2000
DOI: 10.1001/archopht.118.3.344
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Surgery for Choroidal Neovascularization in Patients With High Myopia

Abstract: To analyze the visual outcome in patients undergoing surgical removal of subfoveal choroidal neovascularization (CNV) in eyes with high myopia. Methods: We retrospectively reviewed the medical records of 48 consecutive patients with high myopia (Ն6 diopters [D]) who underwent vitrectomy with surgical removal of subfoveal CNV. The patient population consisted of 2 groups. Group 1 included 23 patients with findings only of myopic degeneration, and group 2 included 25 patients with presumed ocular histoplasmosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…The Subretinal Surgery Trial group reported no benefit of surgical excision in patients with ocular histoplasmosis and idiopathic CNV, and marginal benefit for the subgroup of patients with a VA of 20/100 or worse [67]. Overall, recurrence rates of CNV are high, ranging between 18 and 57% in most studies, and visual demise is not uncommon [68][69][70]. There is at present therefore little evidence to support the surgical excision of CNV in PM.…”
Section: Surgical Approaches To Macular Disease Secondary To Pathologmentioning
confidence: 99%
“…The Subretinal Surgery Trial group reported no benefit of surgical excision in patients with ocular histoplasmosis and idiopathic CNV, and marginal benefit for the subgroup of patients with a VA of 20/100 or worse [67]. Overall, recurrence rates of CNV are high, ranging between 18 and 57% in most studies, and visual demise is not uncommon [68][69][70]. There is at present therefore little evidence to support the surgical excision of CNV in PM.…”
Section: Surgical Approaches To Macular Disease Secondary To Pathologmentioning
confidence: 99%
“…Different therapeutic approaches have been tried for myopic CNV, including argon laser photocoagulation [2,3], surgery [4,5], and photodynamic therapy with verteporfin (PDT) alone [6][7][8], or associated with intravitreal triamcinolone acetonide injection [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Myopic maculopathy is the main cause of vision loss among highly myopic patients, and the leading aetiology of subfoveal choroidal neovascularization (CNV) among patients younger than 50 years of age. 1 Different therapeutic approaches have been tried to treat myopic CNV, including argon laser photocoagulation, 2,3 surgical removal, and macular translocation, 4,5 and, more recently, photodynamic therapy (PDT) with verteporfin. [6][7][8] Visual deterioration secondary to retinal pigment epithelium (RPE) and choriocapillaris atrophy, and the frequent need to repeat PDT sessions have lead to the association of intravitreal triamcinolone and PDT.…”
Section: Introductionmentioning
confidence: 99%